The Effect of Foot Soak Therapy Using Warm Water on the Lowering Blood Pressure in Patients with Essential Hypertension - Mariza Elvira; Debby Sinthania; Debby Silvia Dewi; Aulia Asman; Muhammad Arif (South East Asia Nursing Research, 2023)
Essential hypertension is an increase in blood pressure with no known cause. Management of hypertension can be done non-pharmacologically such as massage, acupuncture, meditation, herbal treatment, and foot soak therapy using warm water. Foot soak therapy using warm water are inexpensive and effective. In 2021, Sungai Sariak Community Health Center patients had hypertension second most often. It provides therapy in the form of drugs like amlodipine, but a nurse interviewed said they had never provided education about foot soak therapy using warm water. The study examined the foot soak therapy using warm water on blood pressure in patients with essential hypertension. This study employed experimental design through Purposive Sampling to choose 25 hypertensive patients. The average systolic blood pressure of people with hypertension before giving foot soak therapy using warm water was 156.96 and after giving foot soak therapy using warm water was 142 .40, the average diastolic blood pressure of people with hypertension before giving foot soak therapy using warm water was 88.44 and after giving foot soak therapy using warm water was 81.44, there was an effect of foot soak therapy using warm water on blood pressure in people with essential hypertension with p value = 0.000 (< 0.05) for the systolic blood pressure variable and for the diastolic blood pressure variable, a p value = 0.006 (< 0.05). Foot soak therapy using warm water has a significant effect on reducing blood pressure in hypertension sufferers.